Pengaruh Kualitas Pelayanan terhadap Kepuasan Nasabah pada PT. Bank Rakyak Indonesia (Persero) Tbk.Unit Kota Ambon - Imran Hatala; Rizki Hlato (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the quality of service to customer satisfaction at PT. Bank Rakyat Indonesia. This type of research uses a qualitative approach and produces descriptive data because it intends to explore and appreciate an object. The data collection technique uses observation/observation techniques and questionnaires (questioners). The satisfaction questionnaire was compiled using satisfaction indicators, namely tangibles, emphaty, reliability, responsiveness, assurance Data analysis was carried out descriptively on the data obtained in the field. Based on the results of the data analysis described by the author in the form of the table above, it can be seen that the quality of service at PT. Bank Rakyat Indonesia (Persero) Tbk. Kota Ambon Unit has not been maximized because there are still customers who are not satisfied with the services provided. services provided by BRI Ambon City Unit. The average item is 2.08. The transaction was 2.78 and this shows that this study is in the fairly good category. The bank guarantees security for customers in making transactions. The average item is 4.1, indicating that the research is included in the very good category and this means that the bank is able to ensure the safety of every customer who makes a transaction